ANALISIS FAKTOR RISIKO ATONIA UTERI - Julizar, Melati; Effendi, jusuf S.; Sukandar, Hadyana (Universitas Tribhuwana Tunggadewi, 2019)
Maternal mortality rate in Indonesia is still relatively high. The biggest cause of maternal mortality in Indonesia is bleeding. Most bleeding in the puerperium (75-80%) is uterine atony. Uterine atony is the most frequent cause of the occurrence of bleeding postpartum. This study aimed to analyze the risk factors for uterine atony in Cut Meutia General Hospital and Health Center PONED in North Aceh district. This study uses a case control design, as a case group, maternal postpartum hemorrhage with uterine atony and control group, maternal postpartum hemorrhage without uterine atony. The sample size for each selected group 69 (the number of cases during the period from 2015 to 2017) while the control selected at random with the same number as many as 69 cases. Data analysis using chi square and multiple logistic regression. The results of the research bivariable indicates a meaningful associated with uterine atony is preeclampsia with OR 10,30 (CI 95%: 2,91-36,41), twin pregnancy with OR 17,31 (CI 95%: 2,21-135,76), induction of labor with an OR 4,39 (CI 95%: 1,0-21,45), grande multipara with OR 4,52 (CI 95%: 1,61-12,73) compared with primipara. Multivariable those associated with uterine atony is the age of the mother with OR 2,98 (CI 95%: 0,56-15,82), preeclampsia with OR 20,27 (CI 95%: 4,66-88,20), induction of labor with an OR 6,69 (CI 95%: 1,12-39,95), twin pregnancy with OR 52,39 (CI 95%: 5,65-486,03), anemia with OR 3,06 (CI 95%: 1,07-8,69). This study concluded that parity, preeclampsia, twin pregnancy and labor induction were risk factors for the incidence of uterine atony with twin pregnancy as the most dominant factor in the incidence of uterine atony. Keywords : Risk factors; Uterine Atony.